Assessment of RFID vehicular access control at the University of the Philippines Diliman campus using traffic microsimulation - Cañete, Iris Joy M.; Macale, Genesis G. (College of Engineering, University of the Philippines Diliman, 2013)
Traffic microsimulation models, if properly developed and calibrated, can be very useful to transportation planners and traffic engineers in assessing alternative traffic schemes and transportation projects. This study developed a calibrated and validated microsimulation model for the prediction of queuing characteristics at the access portals where automation of barrier gates will be implemented. This paper focused on the development of the validated model by testing the model against two most critical time periods which served as data for calibration and validation procedure. Appropriate tests, including statistical tests visual inspection, were undertaken in assessing the success of calibration and validation parameters. Average and maximum queue lengths were compared in evaluating the impact of the alternative on a long-term basis. Results showed that shorter queuing developed at the entering gates while longer queuing and traffic delays were experienced at the exiting gates